Goats and sheep in the traditional livestock production systems in semi-arid northern Africa: Their importance, productivity and constraints on production - Wilson, R.T. (Westview Press, Inc., 1984)
Discusses relative importance & contributions, productivities and constraints to increasing productivity of small ruminants under traditional management systems in the northern drier areas of subsaharan Africa w. emphasis on livestock numbers; role in providing meat & milk esp. to smallholders & during dry periods; resistance to & ability to recover from drought; liveweight production indices; preweaning mortality, diseases & nutrition.